ANALISIS TERHADAP PUTUSAN MAHKAMAH KONSTITUSI NOMOR 93/PUU-X/2012 TENTANG PENYELESAIAN SENGKETA PERBANKAN SYARIAH - Nursal Nursal (Tamwil, 2015)
In this qualitative study, the researcher analyzed the effect of the decision of Constitutional Courts Number 93/PUU-X/2012 about syariah banking by litigation or non litigation. The results of this study were 1) for ligitation, the solving problems on conflict of Syariah Banking were on Religious Courts; 2) for non ligitation, it was the second choice if the consumers did not want to solve the problems on Religious Court, the solving problem was based on discussion; consultation; negositation; mediation; and expert judgment. Keywords: Decision of Constitutional Courts, Syariah Banking, Religious Court, Litigation, Non Litigation